The Power of Modern Value Investing Beyond Indexing, Algos, and Alpha - Smith, Gary; Smith, Margaret (Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
XXIII, 181 p. 83 illus., 5 illus. in color.